Description of the immature stages of Platycrepidius dewynteri Chassain (Coleoptera, Elateridae, Agrypninae, Platycrepidiini) from Brazil with a synopsis of the larval characters of Agrypninae tribes - Rosa, Simone Policena; Albertoni, Fabiano F.; Bená, Daniela De Cassia (Zootaxa, 2015)
Mature larva and pupa of Platycrepidius dewynteri Chassain are described, from Pará state, Brazil. Biological notes under laboratory conditions and comparison with P. bicinctus Candèze are also included. Additionally, we present a synopsis and a morphological comparative study based mainly on literature of the known mature larvae of the Agrypninae genera.